2020
DOI: 10.1029/2019gl085999
|View full text |Cite
|
Sign up to set email alerts
|

Six‐Axis Ground Motion Measurements of Caldera Collapse at Kīlauea Volcano, Hawai'i—More Data, More Puzzles?

Abstract: Near‐field recordings of large earthquakes and volcano‐induced events using traditional seismological instrumentation often suffer from unaccounted effects of local tilt and saturation of signals. Recent hardware advances have led to the development of the blueSeis‐3A, a very broadband, highly sensitive rotational motion sensor. We installed this sensor in close proximity to permanently deployed classical instrumentation (i.e., translational seismometer, accelerometer, and tiltmeter) at the Hawaiian Volcano Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…In seismology, static rotations only occur in the near-field of large earthquakes. Recently, static rotations could be directly observed for the first time during an eruption of the Kilauea volcano using a dedicated rotational seismometer [23]. For weak motion (i.e., seismic waves), the displacement gradient of a deformation in an elastic continuum can be fully described by its symmetric part (i.e., the strain tensor).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…In seismology, static rotations only occur in the near-field of large earthquakes. Recently, static rotations could be directly observed for the first time during an eruption of the Kilauea volcano using a dedicated rotational seismometer [23]. For weak motion (i.e., seismic waves), the displacement gradient of a deformation in an elastic continuum can be fully described by its symmetric part (i.e., the strain tensor).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…An event data base exists (Salvermoser et al, 2017) into which seismic events recorded on the G-ring laser and -as of recently -the ROMY ring laser are written on a daily basis. In the past few years portable broadband sensors that measure rotational ground motions have been developed (Bernauer et al, 2018) and are now being applied in the field (e.g., Yuan et al, 2020b;Wassermann et al, 2020). However, it is important to note that they are approximately three orders of magnitude less sensitive than the ring laser systems, therefore less capable of capturing regular global earthquake-induced wavefields.…”
Section: Earthquake-induced Ground Motionsmentioning
confidence: 99%
“…Many developments of this new field (rotational seismology) in terms of instrumentation, theory, and applications have been documented in recent review articles (Schmelzbach et al, 2018;Igel et al, 2015; van der Baan, 2017) and two special issues (Lee et al, 2009;Igel et al, 2012). From an instrumentation point of view these developments can be subdivided into two categories: 1) the high-resolution observatory-style recording systems like ring lasers as discussed in this paper and 2) portable rotation sensors that only recently are considered fit for the specific requirements of seismic ground observations (e.g., Bernauer et al, 2012Bernauer et al, , 2018Yuan et al, 2020b;Wassermann et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For the purpose of constraining the interior structure of a planetary body, the concepts of seismology play a major role. On Earth, recent studies have shown vital advantages of 6DoF observations compared to the classical 3DoF approach (Wassermann et al 2016;Sollberger et al 2018;Schmelzbach et al 2018;Wassermann et al 2020;Bernauer et al 2020;Yuan et al 2020). Among the major advantages for planetary applications are the following:…”
Section: Dof Seismologymentioning
confidence: 99%